Gettysburg--The Second Day : the Second Day. - Pfanz, Harry W. (Harry Willcox), 1921-2015 (University of North Carolina Press, 1987)
Harry Pfanz, a former historian at Gettysburg National Military Park, has written a definitive account of the second day's brutal combat. He begins by introducing the men and units that were to do battle, analyzing the strategic intentions of Lee and Meade as commanders of the opposing armies, and describing the concentration of forces in the area around Gettysburg. He then examines the development of tactical plans and the deployment of troops for the approaching battle. But the emphasis is on the fighting itself. Pfanz provides a thorough account of the Confederates' smashing assaults--at Dev.